Pengaruh Struktur Kepemilikan Saham, Struktur Modal, Dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Farmasi Yang Terdaftar Di BEI Tahun 2017-2022 - Shabira Prihar Anindita; Dyah Ratnawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research is to evaluate and show the influence of share ownership structure, which is separated into institutional and management ownership, capital structure, and profitability on firm value in pharmaceutical subsector businesses listed on the Indonesia Stock Exchange (IDX) between 2017 and 2022. This is a quantitative analysis based on secondary data from the annual and sustainability reports of pharmaceutical subsector enterprises listed on the Indonesia Stock Exchange between 2017 and 2022. This analysis included pharmaceutical businesses listed on the Indonesia Stock Exchange between 2017 and 2022. The sample research approach employed was quota sampling, which yielded nine firms. The outcomes of this study reveal that institutional ownership, capital structure, and profitability all have an influence on firm value, while management ownership has no impact.